Fungal community, Fusarium head blight complex and secondary metabolites associated with malting barley grains harvested in Umbria, central Italy - Beccari, G.; Senatore, M.; Tini, F.; Sulyok, M.; Covarelli, Lorenzo (Elsevier, 2018)
In recent years, due to the negative impact of toxigenic mycobiota and of the accumulation of their secondary metabolites in malting barley grains, monitoring the evolution of fungal communities in a certain cultivation area as well as detecting the different mycotoxins present in the raw material prior to malting and brewing processes have become increasingly important. In this study, a survey was carried out on malting barley samples collected after their harvest in the Umbria region (central Italy). Samples were analyzed to determine the composition of the fungal community, to identify the isolated Fusarium species, to quantify fungal secondary metabolites in the grains and to characterize the in vitro mycotoxigenic profile of a subset of the isolated Fusarium strains. The fungal community of barley grains was mainly composed of microorganisms belonging to the genus Alternaria (77%), followed by those belonging to the genus Fusarium (27%). The Fusarium head blight (FHB) complex was represented by nine species with the predominance of Fusarium poae (37%), followed by Fusarium avenaceum (23%), Fusarium graminearum (22%) and Fusarium tricinctum (7%). Secondary metabolites biosynthesized by Alternaria and Fusarium species were present in the analyzed grains. Among those biosynthesized by Fusarium species, nivalenol and enniatins were the most prevalent ones. Type A trichothecenes (T-2 and HT-2 toxins) as well as beauvericin were also present with a high incidence. Conversely, the number of samples contaminated with deoxynivalenol was low. Conjugated forms, such as deoxynivalenol-3-glucoside and HT-2-glucoside, were detected for the first time in malting barley grains cultivated in the surveyed area. In addition, strains of F. avenaceum and F. tricinctum showed the ability to biosynthesize in vitro high concentrations of enniatins. The analysis of fungal secondary metabolites, both in the grains and in vitro, revealed also the presence of other compounds, for which further investigations will be required. The combination of microbiological analyses, of molecular biology assays and of multi-mycotoxin screening shed light on the complexity of the fungal community and its secondary metabolites released in malting barley.